Antecedents of Patient Experiential Satisfaction and its Impact on Patient Loyalty (A Study of Obstetric Service in a Mother and Child Hospital in Indonesia) - Agus Heriyanto; Ferdi Antonio (Universitas Pelita Harapan, 2022)
The purpose of this study was to examine and analysed the effect of maternity care by doctors, maternity care by nurse, hospital ambiance, hospital reputation, waiting time, and patient safety on patient experiential satisfaction and their impact on patient loyalty moderated by social media engagement. The analysis of this modified research model from previous studies was carried out with data from obstetric services at the Mother and Child Hospital or Rumah Sakit Ibu dan Anak (RSIA). The method in this research is quantitative with a survey and cross-sectional approach. Respondent data were taken by purposive sampling with a questionnaire from individuals who had received obstetric services at RSIA XYZ, especially those who had a history of giving birth at this RSIA. There were 205 samples that met the requirements and were analysed by PLS-SEM. The results showed that the six antecedents of patient experiential satisfaction were proven to have a significant and positive effect. The strongest influence was shown by maternity care by doctors and followed by hospital reputation and hospital ambiance. The findings of this study prove the positive impact of experiential satisfaction on patient loyalty at RSIA. Social media engagement was found to have a significant and negative effect, this can be attributed to the suboptimal performance of social media managed by RSIA. From the findings of this study, managerial implications can be drawn for the development of obstetric services at RSIA. There are a number of limitations that are followed by suggestions for further research.